Evaluation of Iberian pig carcasses based on NIR spectra of pork loins - De Pedro E.; De la Haba J.; Núñez N.; García J.; Garrido A. (5. International Symposium on the Mediterranean Pig, 2007)
The objective of this paper is to develop multivariate models based on NIR spectral data from Iberian pork loins to determine the quality of the carcass. The official methods to evaluate carcass quality have different limitations. Thus, it is necessary to find new methods to classify carcasses according to their feeding regime. Near Infrared Spectroscopy (NIRS) allows quick analysis to be obtained with low cost per sample, high accuracy, and easy handling. Loin samples were taken from Iberian pigs. The feeding regime was: exclusively grass and acorn for 104 days (B1) and 83 days (B2), grass and acorns, supplemented with a commercial compound feed during the last 13 days (R) and only commercial compound feed (C). Lineal discriminant analysis was used to obtain a multivariate model based on NIR spectra. The model results show that all the samples from group C were correctly classified.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)